The Modern Middle East : A Reader - Edited By Albert Hourani; Philip S Khoury and Mary C Wilson (London I.B. Tauris & Co Ltd, 1993)
This textbook assembles key writings on the modern history of the Middle East by some of the most distinguished specialists in the field. The book aims to meet the needs of a wide range of students.
Include Notes
"The Reader is designed to complement parts III-V of A History of the Arab Peoples"--Preface.
Keywords: Middle East -- Europe -- Politics and Government